Association of the vitamin D receptor gene polymorphism with sex- and non-sex-associated cancers: A meta-analysis - Lukasz Laczmanski; Felicja Lwow; Anna Osina; Martyna Kepska; Izabela Laczmanska; Wojciech Witkiewicz (Tumor Biology)
Currently higher morbidity and mortality rates are observed in cancer diseases, especially sex-dependent cancers. A positive role of endogenous vitamin D concentration in cancer diseases has been reported in many publications. Furthermore, there has been observed a relationship between serum vitamin D and testosterone concentrations in an elderly Caucasian population carrying the vitamin D receptor FokI gene polymorphism. The aim of this study was to investigate whether the vitamin D receptor FokI polymorphism is associated with cancerogenesis in sex-dependent cancers. The MEDLINE and ResearchGate databases were used to search for articles up to January 2017, and 96 articles concerning the FokI polymorphism were chosen. Odds ratios with 95% confidence intervals were used to assess the strength of associations between polymorphisms of vitamin D receptor and cancer risk in the described populations. The fixed-effects model and the DerSimonian–Laird random-effects model (with weights based on the inverse variance) were used to calculate summary odds ratios, and both within- and between-study variation were considered. Generally, the F variant reduces the risk of cancer by 4% (odds ratio = 0.96, p value = 0.0057). This effect is particularly evident in female sex–associated cancers (odds ratio = 0.96, 95% confidence interval: 0.93–0.99, p value = 0.0259), but it is not observed in non-sex-associated cancers. Polymorphism FokI is associated with breast and ovarian cancers.